STUDY OF THE POTENTIAL REDUCTION OF THE CARBON FOOTPRINT FROM THE REPLACEMENT OF LPG BY WOOD PELLETS APPLIED TO THE PROVINCE OF ENTRE RÍOS, ARGENTINA (Journal of Industrial and Mechanical Engineering, 2022)
Climate change is one of the problems that most worries countries worldwide given the number of consequences it entails.It finds its cause in the greenhouse gas emissions that are released into the atmosphere by various activities, although one of the main ones is the generation of energy.In Argentina this concern is not minor, given that our energy matrix is composed mostly of fossil fuels, which are the main emitters of these gases, causing us to actively contribute to this issue.In this context, this article seeks to analyse the carbon footprint generated by the use of LPG and compare it with that produced by wood pellets manufactured based on waste from forest industries in the province of Entre Ríos.The study was carried out by comparing the carbon footprint produced by the amount of LPG that is estimated to be replaced in the province, against the footprint that would be produced if these wood pellets produced, by waste from sawmills, were used.Taking into account that only 20% of the LPG can be replaced, given the availability of these wastes, and although the fact that they generate gases during their combustion, the analysis showed that the replacement would generate 14% less CO2 eq.
Keywords: footprint; carbon; pellets; wood; liquified gas; energy; GHG; greenhouse effect